Resource bricolage and growth of product and market scope in social enterprises. Issue 3 (15th March 2018) - Tasavori, Misagh; Kwong, Caleb; Pruthi, Sarika
Abstract: This research aims to understand how resource bricolage strategy plays a role in the growth of social enterprises in terms of their product and market. Based on interviews with nine social enterprises, our exploratory finding suggests that social enterprises often employ both internal and network resources in the process of making do. We further explore the relationship between the form of resource utilisation and the nature and scope of activities that the social enterprises embark upon, and find that only those relying on both internal and network bricolage are able to expand into new markets utilising newly developed products. We also find that social enterprises relying on only internal resources can reach the same point through incremental improvisation, by first moving towards either product extension or market expansion, before then embarking on the other. This research contributes to the social entrepreneurship literature by enhancing our understanding of the relationship between resource bricolage strategy and growth of social enterprises through product/ market scope in a penurious environment. The findings of this research also have implications for social enterprise managers and policy makers in utilising their resources and responding to environmental opportunities and challenges.